Astrogliosis in multiple sclerosis and neuro-inflammation: what role for the notch pathway? - Mora, Pierre; Chapouly, Candice (Frontiers in Immunology, 2023)
Multiple sclerosis is an autoimmune inflammatory disease of the central nervous system leading to neurodegeneration. It affects 2.3 million people worldwide, generally younger than 50. There is no known cure for the disease, and current treatment options -mainly immunotherapies to limit disease progression -are few and associated with serious side effects. In multiple sclerosis, disruption of the blood-brain barrier is an early event in the pathogenesis of lesions, predisposing to edema, excitotoxicity and inflammatory infiltration into the central nervous system. Recently, the vision of the blood brain barrier structure and integrity has changed and include contributions from all components of the neurovascular unit, among which astrocytes. During neuro-inflammation, astrocytes become reactive. They undergo morphological and molecular changes named "astrogliosis" driving the conversion from acute inflammatory injury to a chronic neurodegenerative state. Astrogliosis mechanisms are minimally explored despite their significance in regulating the autoimmune response during multiple sclerosis. Therefore, in this review, we take stock of the state of knowledge regarding astrogliosis in neuro-inflammation and highlight the central role of NOTCH signaling in the process of astrocyte reactivity. Indeed, a very detailed nomenclature published in nature neurosciences in 2021, listing all the reactive astrocyte markers fully identified in the literature, doesn't cover the NOTCH signaling. Hence, we discuss evidence supporting NOTCH1 receptor as a central regulator of astrogliosis in the pathophysiology of neuro-inflammation, notably multiple sclerosis, in human and experimental models.